2017
DOI: 10.1016/j.sjbs.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Self-medication and antibiotic resistance: Crisis, current challenges, and prevention

Abstract: The present study aims to explore the crisis of antibiotic resistance and discover more about the current challenges related to self-medication. The current challenges related to antibiotic resistance are unique and differ from the challenges of the past since new bacterial pathogens are involved and continue to evolve. Strains with resistance to multiple antibiotic classes have emerged which the discovery of new antibiotics has failed to match. The consequences of antibiotic resistance are grave with mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
240
0
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(257 citation statements)
references
References 22 publications
4
240
0
13
Order By: Relevance
“…Finally, it is vitally important to target patients and the public in any future initiatives as they can put pressure on physicians, pharmacists and nurses to prescribe and dispense antibiotics for URTIs 98,157,208,374 . People vary in their knowledge about antibiotics and AMR; however, and they can have strong beliefs about the effectiveness of antibiotics even for viral infections 104,137,157,248,[375][376][377] .…”
Section: Patients and The Publicmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, it is vitally important to target patients and the public in any future initiatives as they can put pressure on physicians, pharmacists and nurses to prescribe and dispense antibiotics for URTIs 98,157,208,374 . People vary in their knowledge about antibiotics and AMR; however, and they can have strong beliefs about the effectiveness of antibiotics even for viral infections 104,137,157,248,[375][376][377] .…”
Section: Patients and The Publicmentioning
confidence: 99%
“…Sub-optimal management of URTIs in LMICs including the overuse of antibiotics is promoted by misconceptions, social-cultural issues, diagnostic uncertainty, and clinical competency as well as commercial, patient and time pressures 21,29,50,52,57,92,[96][97][98][99][100][101][102][103][104][105][106][107][108][109] . Inappropriate management is also a concern in countries with high rates of infectious diseases such as HIV, malaria and tuberculosis (TB), which is the case in sub-Saharan Africa, as this may complicate treatment [110][111][112] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that in India the prevalence of selfmedication was 37% & 17% in urban and rural population respectively [23]. Several studies show that self-medication is a global phenomenon resulting in major problems of wastage of resourses, increased drug resistance and causes serious health hazards such as adverse reactions and prolonged suffering [24][25][26]. The issue of medication misuse is not isolated to India alone, but it is an issue that needs to be addressed in any context where pharmaceuticals are widely available.…”
Section: Self Medication and Antibiotic Resistancementioning
confidence: 99%
“…Although a number of antibiotics are commercially available for various infections but the development of microbial resistance is another challenge which is due to overuse of antibiotics and poor infection control practices [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%